Psilocybin occasioned mystical-type experiences: Immediate and persisting dose-related effects - Griffiths, R. R. (2011)
RATIONALE: This dose-effect study extends previous observations showing that psilocybin can occasion mystical-type experiences having persisting positive effects on attitudes, mood, and behavior. OBJECTIVES: This double-blind study evaluated psilocybin (0, 5, 10, 20, 30 mg/70 kg, p.o.) administered under supportive conditions. METHODS: Participants were 18 adults (17 hallucinogen-naïve). Five 8-hour sessions were conducted individually for each participant at 1-month intervals. Participants were randomized to receive the four active doses in either ascending or descending order (9 participants each). Placebo was scheduled quasi-randomly. During sessions volunteers used eyeshades and were instructed to direct their attention inward. Volunteers completed questionnaires assessing effects immediately after and 1 month after each session, and at 14 months follow-up. RESULTS: Psilocybin produced acute perceptual and subjective effects including, at 20 and/or 30 mg/70 kg, extreme anxiety/fear (39% of volunteers) and/or mystical-type experience (72% of volunteers). One month after sessions at the two highest doses, volunteers rated the psilocybin experience as having substantial personal and spiritual significance, and attributed to the experience sustained positive changes in attitudes, mood, and behavior, with the ascending dose sequence showing greater positive effects. At 14 months, ratings were undiminished and were consistent with changes rated by community observers. Both the acute and persisting effects of psilocybin were generally a monotonically increasing function of dose, with the lowest dose showing significant effects. CONCLUSIONS: Under supportive conditions, 20 and 30 mg/70 kg psilocybin occasioned mystical-type experiences having persisting positive effects on attitudes, mood and behavior. Implications for therapeutic trials are discussed.